PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATERI KUBUS DAN BALOK UNTUK SISWA KELAS VIII SMP/MTS - Tantri Irani, Zea Sarah; Solfitri, Titi; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this study is the restrict of mathematics learning instruments as supporting learning referring to 2013 Curriculum. This study aimed to develop mathematics learning instruments with problem based learning’s model on cubes and cuboids for 8th grade SMP/MTs. Learning instruments in this study are syllabus, lesson plans, and student worksheet. This study method used is 4D model by Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel that consist of define, design, development, and disseminate, but the study was limited only to development step. Based on the data analysis, it can be conclude that mathematics learning instruments is very valid with mean score of syllabus is 4,53, mean score of lesson plans is 4,26, and mean score of student worksheet is 4,21. This student worksheet has also reached the practical qualification with mean percentage of student responses is 97,33 on a small test group.Keyword: Mathematics Learning Instrument, Problem Based Learning, Research and Development.